2013
DOI: 10.2190/pm.45.2.a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical and Psychological Comorbid Conditions on the Quality of Life of Patients with Acute Myocardial Infarction: A Multi-Center, Cross-Sectional Observational Study from Turkey

Abstract: Female patients are more prone to impairment in quality of life after myocardial infarction. Both comorbid medical conditions and depression have a significant impact on the impairment of QoL in Turkish patients with acute MI. In order to improve the subjective wellbeing of post MI patients, both psychiatric and physical comorbidities must be detected and managed even in the short-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Our study revealed that PCS QOL was generally worse with increasing number of comorbidities. Such findings were seen in several studies [32][33][34]. Patients with CVD with osteoarthritis comorbidity were found to have poorer physical health [35] and those with chronic obstructive pulmonary disease exhibited poorer physical fitness [36].…”
Section: Discussionmentioning
confidence: 61%
“…Our study revealed that PCS QOL was generally worse with increasing number of comorbidities. Such findings were seen in several studies [32][33][34]. Patients with CVD with osteoarthritis comorbidity were found to have poorer physical health [35] and those with chronic obstructive pulmonary disease exhibited poorer physical fitness [36].…”
Section: Discussionmentioning
confidence: 61%
“…A possible reason for this might be the chronic nature, severity, and long-term antihypertensive and antidiabetic medication use together with lifestyle and behavior change to adjust to the illness may impose an added stress burden on patients, and this affects their HRQL negatively. This could also be due to the contributions of different chronic diseases in patients with MI and the side effects of the different drugs or drug interactions, which impair overall HRQL (Sertoz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for this might be the chronic nature, severity, and long-term antihypertensive medication use together with lifestyle and behavior change to adjust to the illness may impose an added stress burden on patients, and this affects their HRQoL negatively. This could also be due to the contributions of different chronic diseases in patients with MI and the side effects of the different drugs or drug interactions, which impair overall HRQoL [35,48].…”
Section: Discussionmentioning
confidence: 99%